Preoperative airway predictive tests: How far are we from the books? - Babatunde B Osinaike (Indian Journal of Health Sciences and Biomedical Research KLEU, 2016)
Background: Many preoperative airway assessment tests to predict a difficult intubation (DI) have been developed and documented, but we have no published data on how frequently these tests are used or how useful they are perceived by anesthetists in Nigeria. This survey was done among physician anesthetists in Nigeria to document practices related to the use of bedside airway predictive tests in adults. Methods: The following tests were compiled into a questionnaire and administered to physician anesthetists in training. Effective mandibular length, inter-incisor gap (IIG), Mallampati classification (MC), sternomental distance, thyromental distance, hyomental distance (HMD), range of neck motion (ROM), upper lip bite test (ULBT), mandibular protrusion test, and prayer sign (PS). A 5 and 4-level Likert item was used to assess the frequency of use and perceived importance of each test during the preoperative period. Results: A total of 81 (90%) participants completed the questionnaires. Of the 10 predictive tests listed; MC and ROM were "always" and "very often" used in 80 (98.8%) and 67 (82.7%) of participants, while PS, ULBT, and HMD is "rarely" or "never used" in 42 (51.9%), 41 (50.6%), and 39 (48.2%) of participants, respectively. MC, ROM, and IIG assessments were considered "very useful" and "useful" in 76 (93.8%), 69 (85.2%), and 69 (85.2%) of participants respectively in predicting DI, while HMD and PS were considered to be of "little use" by 7 (8.6%) and 7 (8.6%) of participants, respectively. MC, ROM, and IIG measurement (28%) were perceived as the best combination for high predictive value for DI. Conclusion: There is a tendency towards the use of MC and ROM more frequently than other tests during bedside preoperative airway assessment in adults by physician anesthetists in Nigeria. This practice may be insufficient for the prediction of DI in view of the current evidence.